2017
DOI: 10.1103/physrevlett.118.178002
|View full text |Cite
|
Sign up to set email alerts
|

Fast Diffusion of Long Guest Rods in a Lamellar Phase of Short Host Particles

Abstract: We investigate the dynamic behavior of long guest rodlike particles immersed in liquid crystalline phases formed by shorter host rods, tracking both guest and host particles by fluorescence microscopy. Counterintuitively, we evidence that long rods diffuse faster than short rods forming the one-dimensional ordered smectic-A phase. This results from the larger and noncommensurate size of the guest particles as compared to the wavelength of the energy landscape set by the lamellar stack of liquid slabs. The long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…On the other hand, the diffusion of non-spherical particles in anisotropic liquid crystalline environments is still largely unexplored. Recently, Alvarez et al [9] studied in experiments the diffusion of tracer amounts of non-commensurate guest viral rods in a smectic phase of shorter host fd filamentous viruses with a size ratio L guest /L host ≃ 1.3. Surprisingly they found that while the host particles experience the usual hopping-type dynamics across smectic layers, the noncommensurate guest particles undergo a fast and almost continuous nematic-like diffusion, yielding the exceptional case of larger guest particles diffusing faster than the smaller host ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the diffusion of non-spherical particles in anisotropic liquid crystalline environments is still largely unexplored. Recently, Alvarez et al [9] studied in experiments the diffusion of tracer amounts of non-commensurate guest viral rods in a smectic phase of shorter host fd filamentous viruses with a size ratio L guest /L host ≃ 1.3. Surprisingly they found that while the host particles experience the usual hopping-type dynamics across smectic layers, the noncommensurate guest particles undergo a fast and almost continuous nematic-like diffusion, yielding the exceptional case of larger guest particles diffusing faster than the smaller host ones.…”
mentioning
confidence: 99%
“…Similarly, for guest rods shorter than the smectic layer spacing, the time interval of caging decreases (r ∼ 0.47) and eventually disappears for guest particles of low anisotropy (r ∼ 0.29). [9]. The inset shows the raw diffusion coefficients.…”
mentioning
confidence: 99%
“…The most promising and thus exploited are filamentous phages, i.e., Ff, f1, Ike, fd, Pf1, and M13. Their length (up to 800 nm) and width (down to 8 nm) are perfect for the synthesis of nanowires and the fibrous components of composites [ 99 , 153 , 154 , 155 , 156 , 157 ].…”
Section: Bacteriophages In Materials Sciencementioning
confidence: 99%
“…While most of the existing studies address structural properties, less is known about the dynamic behavior of anisotropic particles. The most well-studied systems in this regard are perhaps colloidal rods and ellipsoids (1)(2)(3)(4)(5)(6)(7)(8)(9). However, because most of these studies involved particle tracking, they are therefore limited to quasi-2D (two dimension) and to self-diffusion.…”
Section: Introductionmentioning
confidence: 99%